CONTEXTUAL LEARNING IN ENVIRONMENTAL EDUCATION PROGRAM AND STUDENTS’ ATTITUDE ON HEALTH EFFECTS OF MERCURY: A RASCH MODELING ANALYSIS - Sumintono, Bambang (Jurnal Pengajaran MIPA, 2018)
Environmental issues from pollution to climate change are a major concern in today’s world in which mining activities and its attributed pollution effects posed a looming threat to the environment and human health. This study examines how the implementation of contextual learning in environmental education program could alter students’ attitude on the health effects of mercury. Respondents were 165 junior high school students in Aceh Province-Indonesia. Students’ attitude on the health effects of mercury was explored via a questionnaire administered before and after learning, and the collected data was analyzed by Rasch Modeling. Rasch modeling indicated that contextual learning significantly alters students’ attitude on the health effects of mercury. Students’ attitude changes before and after learning are discussed.